How to cheat at securing a wireless network - Hurley, Chris (Rockland, Mass. : Syngress, 2006)
Wireless connectivity is now a reality in most businesses. Yet by its nature, wireless networks are the most difficult to secure and are often the favorite target of intruders. This book provides the busy network administrator with best-practice solutions to securing the wireless network With the increased demand for mobile connectivity and the decrease in cost and in the time required for installation, wireless network connections will make up 20% of all corporate network connections by the end of 2006. With this increase in usage comes a commensurate increase in the networks vulnerability to intrusion. This book provides the typical network administrator with the basic tools and instruction they need to maintain a secure network while allowing acceptable access to users. A practical product and technology specific guideline to securing a wireless networks for the busy System Administrator Takes a simplified multi-layered approach into easily deployed plans for a straight forward understanding Does not bog you down with history, but offers practical useful information for today.
Introduction to wireless : from past to present -- Wireless security -- Dangers of wireless devices in the workplace -- WLAN rogue access point detection and mitigation -- Wireless LAN VLANs -- Designing a wireless network -- Wireless network architecture and design -- Monitoring and intrusion detection -- Designing a wireless enterprise network : hospital case study -- Designing a wireless industrial network : retail case study -- Designing a wireless home network : home office case study -- Wireless penetration testing.
Includes index.
Keywords: Wireless LANs -- Security measures; Computer networks -- Security measures; Electronic books; Handbooks, manuals, etc